Effects of behavior change techniques in interventions promoting condom use among youth in the Global North - Alcira de Vries; Janneke C. M. Heijne; John B. F. de Wit; Chantal den Daas (PLoS ONE, 2025)
Background Declines in condom use among the general young population highlight the need for effective interventions to prevent sexually transmitted infections and unwanted pregnancies. With this study, we aim to examine the relationship between Behavior Change Techniques (BCTs, the active components of interventions) and the effects of condom interventions among youth. We quantify the number of BCTs used in the interventions, assess their alignment with underlying behavioral theory, and evaluate coverage of specified Mechanisms of Action (MoA, underlying process through which behavior may be influenced) within the behavioral theory. Methods Face-to-face theory-based interventions aiming to promote condom use among youth were identified in a previous systematic review. Interventions were analyzed using the BCT Taxonomy v.1.0., alignment with theory was determined using the Theories and Techniques tool. Wilcoxon rank-sum tests assessed BCT effectiveness. Spearman’s rank correlation coefficient determined associations between intervention effects and the total number of BCTs, the proportion of BCTs aligned with MoAs, and the proportion of MoA covered by BCTs. Results In 21 interventions we identified a median of 3 BCTs (IQR = 1–5) per intervention. BCTs were poorly reported. No grouping of BCTs was associated with more intervention effects on increasing condom use. Neither the proportion of BCTs aligned with the MoAs of the underlying theory in the intervention (median = 85.7%, IQR = 50.0–100%, Spearman’s ρ = −0.09) nor the proportion of MoAs of the underlying theory covered by at least one BCT in the intervention (median = 44.4%, IQR = 25.0–50.0%, Spearman’s ρ = 0.27) were correlated with intervention effects. Conclusions This study provides initial insights into the use of BCTs and the application of behavioral theory in theory-based condom promotion interventions targeting the general young population. No associations between the use of BCTs and the intervention effects on condom use were found. Robust conclusions regarding the utilization of BCTs, their alignment with theory, and their effects can only be reached when future research consistently and comprehensively reports the use of BCTs.